Low blood glucose levels and other complications during growth hormone supplementation in sepsis - Faintuch, Joel; Leme, Renata B. A.; Cruz, Maria Emilia L. F.; Lima, Angela M. B.; Giannella Neto, Daniel; Gama-Rodrigues, Joaquim J. (Revista do Hospital das Clínicas, 1999)
Blood glucose levels in the high normal range or even moderate hyperglycemia is the expected profile in septic postoperative patients receiving high-calorie enteral alimentation. The addition of growth hormone as an anabolic agent should additionally reinforce this tendency. In a cancer patient undergoing partial gastrectomy with lymphadenectomy and suffering from postoperative subphrenic abscess and prolonged sepsis, tube feeding (38.3 kcal/kg/day) and growth hormone (0.17 IU/kg/day) were simultaneously administered for 25 days. Blood glucose levels were in the lower limits of the normal range before growth hormone introduction, and continued with a similar tendency during most of the therapeutic period. Two additional complications, namely heart arrest and peripheral edema, were documented during the same period. It is concluded that sepsis was the most likely mechanism for low glucose values, and that high-calorie enteral diet and growth hormone supplementation did not prevent that result. It is uncertain whether heart arrest was due to the drug, but its association with peripheral edema is well documented in clinical series.